Holding the line: Provider and patient perspectives on Medications for Opioid Use Disorder continuity during the war in Ukraine - Iryna Pykalo; Myroslava Filippovych; Oleksandr Zeziulin; Sergii Dvoriak; Lauren Dayton; Carl Latkin (PLoS ONE, 2026)
Background Ukraine has one of the highest rates of opioid use in Eastern Europe, with an estimated 346,900 people who inject drugs (PWID). Medications for opioid use disorder (MOUD) are critical for reducing opioid-related harms, including HIV transmission. However, the full-scale Russian invasion of Ukraine in February 2022 significantly disrupted MOUD services. Although the Ukraine public health system has worked to address displacement and disruptions, the ongoing armed conflict exacerbated long-standing structural challenges in the Ukrainian addiction treatment system, leading to displacement of patients and providers, damage to infrastructure, and interruptions in medication supply. Methods This qualitative study explores the barriers and facilitators to MOUD access and retention during wartime. Semi-structured interviews were conducted between September and November 2022 with 10 MOUD patients who had been displaced due to the war and 7 healthcare providers in three Ukrainian cities (Lviv, Poltava, Ivano-Frankivsk) that received large numbers of internally displaced persons (IDPs). All patients had been enrolled in MOUD prior to the invasion and continued treatment in their new locations. Data were analyzed using the Rapid Assessment Procedure (RAP) framework to identify thematic patterns across settings and perspectives. Results Both providers and patients reported a range of systemic, logistical, and emotional challenges affecting continuity of care. Key barriers included loss of medical records, reduced dosing due to medication shortages, delayed access for new patients, and financial hardship. Providers also described increased workloads, staff shortages, and lack of emergency preparedness. Patients often relied on peers, non-governmental organisations (NGOs), and informal channels to locate MOUD sites. Despite adversity, many patients remained committed to treatment. Providers adopted flexible, sometimes unofficial practices to sustain care delivery. Conclusions This study highlights the fragility but also resilience of MOUD services in a conflict setting. Findings emphasize the need for policy reforms that institutionalize emergency flexibility, strengthen referral systems, support frontline staff, and integrate peer and civil society support into the national MOUD strategy. Ensuring uninterrupted access to MOUD during crises is vital for public health and for protecting the rights of people who use drugs.